CLIPB10 is a Terminal Protease in the Regulatory Network That Controls Melanization in the African Malaria Mosquito Anopheles gambiae - Zhang, Xin; Li, Miao; El Moussawi, Layla; Saab, Sally; Zhang, Shasha; Osta, Mike A.; Michel, Kristin (Frontiers in Cellular and Infection Microbiology, 2021)
Humoral immune responses in animals are often tightly controlled by regulated proteolysis. This proteolysis is exerted by extracellular protease cascades, whose activation culminates in the proteolytic cleavage of key immune proteins and enzymes. A model for such immune system regulation is the melanization reaction in insects, where the activation of prophenoxidase (proPO) leads to the rapid formation of eumelanin on the surface of foreign entities such as parasites, bacteria and fungi. ProPO activation is tightly regulated by a network of so-called clip domain serine proteases, their proteolytically inactive homologs, and their serpin inhibitors. In Anopheles gambiae, the major malaria vector in sub-Saharan Africa, manipulation of this protease network affects resistance to a wide range of microorganisms, as well as host survival. However, thus far, our understanding of the molecular make-up and regulation of the protease network in mosquitoes is limited. Here, we report the function of the clip domain serine protease CLIPB10 in this network, using a combination of genetic and biochemical assays. CLIPB10 knockdown partially reversed melanotic tumor formation induced by Serpin 2 silencing in the absence of infection. CLIPB10 was also partially required for the melanization of ookinete stages of the rodent malaria parasite Plasmodium berghei in a refractory mosquito genetic background. Recombinant serpin 2 protein, a key inhibitor of the proPO activation cascade in An. gambiae, formed a SDS-stable protein complex with activated recombinant CLIPB10, and efficiently inhibited CLIPB10 activity in vitro at a stoichiometry of 1.89:1. Recombinant activated CLIPB10 increased PO activity in Manduca sexta hemolymph ex vivo, and directly activated purified M. sexta proPO in vitro. Taken together, these data identify CLIPB10 as the second protease with prophenoloxidase-activating function in An. gambiae, in addition to the previously described CLIPB9, suggesting functional redundancy in the protease network that controls melanization. In addition, our data suggest that tissue melanization and humoral melanization of parasites are at least partially mediated by the same proteases.